Determination of both acute and sub acute liver and renal toxicity of Croton palanostigma (sangre de grado) latex in experimental animals - Sandoval, Miguel (2005)
Objective: To determine liver and renal toxicity of Croton palanostigma latex oral swallowing, in therapeutic and larger doses. Materials and Methods: Sixty albino male rats were studied in two groups: one group swallowed for a short time during 7 days and another group swallowed ad libitum during 30 days. In each group there were 3 subgroups: (A) 1/1000 diluted latex (therapeutic dose), (B) 1/100 diluted latex, (C) water (control group). The animal weight and the water or diluted latex consumption were measured. Then, the rats were given ether anesthesia, their blood was obtained by cardiac puncture and centrifuged at 5000 rpm during 5 minutes to obtain plasma. Alkaline phosphatase and transferase glutamyl gamma activity were measured; urea, creatinine, total protein, albumin and globulin levels were studied by espectrophotometry. Results: The average latex consumption in the first group were: in A, 0,14 mL/kg-1/day-1/rat-1; in B, 1,34 mL/kg-1/day-1/ rat-1; and, in C, water. There was no significative difference in the daily latex consumption between the 7 and 30-day trated groups. Both the alkaline phosphatase and transferase glutamyl gamma activities, the blood metabolites and both animal liver/weight ratio and animal renal/weight ratio did not present any significative difference (p>0,05) from the control group. Conclusions: In experimental conditions, the short time and long time sangre de grado oral swallowing, in both therapeutic dose and larger concentrations, did not produce any biochemical, liver or renal alteration in the animals.